Mont Pèlerin 1947 - Bruce Caldwell (Duke University, Center for the History of Political Economy (CHOPE), 2020)
This paper is the first draft of the first substantive chapter of volume 2 of my biography with Hansjoerg Klausinger of F. A. Hayek. It looks at the first meeting of the Mont Pèlerin Society.
Keywords: 330